Toward the construction of integrated physical and genetic maps of the mouse genome using interspersed repetitive sequence PCR (IRS-PCR) genomics. - Hunter, K W; Riba, L; Schalkwyk, L; Clark, M; Resenchuk, S; Beeghly, A; Su, J; Tinkov, F; Lee, P; Ramu, E; Lehrach, H; Housman, D

(untitled) (Genome Research, 1996)
Using two recently developed techniques, IRS-PCR YAC walking and IRS-PCR genotyping, a framework-integrated physical and genetic map of the mouse genome was constructed. The map consists of 821 contigs, containing 7746 YAC clones originating from three different YAC libraries. Three hundred eighty of the contigs have been anchored to the genetic map. Approximately 16% of the physical length of the mouse genome is estimated to be represented.